Prophylactic cholecystectomy: A valuable treatment strategy for cholecystolithiasis after gastric cancer surgery - Liu, Haipeng; Liu, Jie; Xu, Wei; Chen, Xiao (Frontiers in Oncology, 2022)
The main treatment for gastric cancer is surgical excision. Gallstone is one of the common postoperative complications of gastric cancer. In order to avoid the adverse effects of gallstone formation after gastric cancer surgery, we systematically reviewed the factors of gallstone formation after gastric cancer surgery and the evidence of preventive cholecystectomy during gastric cancer surgery.The research progress of cholecystolithiasis formation after gastric cancer surgery was systematically reviewed. The main outcome measures were the incidence of gallstone after gastric cancer surgery, the time of gallstone formation, intervention measures, and the risk of preventive cholecystectomy.The formation of gallstones after gastric cancer surgery is multifactorial, including vagal nerve resection, intestinal hormone secretion mechanism, changes in bile composition, Oddis sphincter dysfunction, type of digestive tract reconstruction, gastrectomy, age, diabetes, gallbladder capacity, etc. The 13 studies included in this review.The most important causes of gallstone formation after gastric cancer surgery may be vagal nerve injury and changes in intestinal hormone secretion mechanism, but its pathophysiological mechanism is still unclear and needs extensive research. Currently, for low-risk patients, we recommend observation, pharmacological prophylaxis, and elective surgical intervention. For patients with high risk factors for postoperative gallstone formation, we suggest that active drug prophylaxis or PC therapy can be considered, but its clinical value needs to be further confirmed by multi-center, prospective studies around the world.